Differential gene expression in activated monocyte-derived macrophages following binding of factor VIIa to tissue factor - Muth, Heidrun; Kreis, Ingo; Zimmermann, Rene; Tillmanns, Harald; Hölschermann, Hans (Thrombosis and Haemostasis, 2005)
Factor VIIa/tissue factor (FVIIa/TF) interaction has been reported to induce intracellular signalling in cells constitutively expressing TF, independently of downstream activation of the coagulation cascade. It is unknown, however, whether binding of FVII to its cofactor TF alters the gene expression profile in cells which inducible express TF under inflammatory conditions. To address this issue, gene expression patterns in cultured LPSstimulated monocyte-derived macrophages with or without exposure to FVIIa were compared by cDNA macro-array analysis. Of the 1176 genes examined on the array, a small set of six genes (IL-6, IL-8, TNF-a, GRO-beta alpha-thymosin, cathepsin H) were consistently up-regulated and one gene suppressed (alpha-antitrypsin) in response to FVIIa in activated monocyte-derived macrophages. Among the seven genes identified by array analysis, five genes were finally confirmed by real-time RT-PCR. Interestingly, all of these genes differentially regulated in response to FVIIa (GRO-beta, IL-6, IL-8, TNF-α and alpha-antitrypsin) are critical in inflammation. The changes in gene expression were reflected by corresponding changes in the protein concentrations of IL-6 and IL-8 as demonstrated by ELISA. Active site-inhibited FVIIa had no effect on gene expression indicating that FVIIa-induced gene alteration is dependent on the proteolytic activity of FVIIa. The FVIIa-induced alterations in gene expression were found to be TF-dependent but independent of downstream coagulation proteins like thrombin and FXa. In summary, this study demonstrates that binding of FVIIa to its cofactor TF enhances restricted pro-inflammatory genes in activated monocyte-derived macrophages. By up-regulation of chemokines critical for leukocyte recruitment, FVIIa/TF interaction on activated monocyte- derived macrophages could be relevant to prepare monocytes/ macrophages for extravasation and may represent a novel amplification loop of leukocyte recruitment.
Keywords: Factor VIIa; monocyte; inflammation; coagulation; gene expression